2009
DOI: 10.1603/022.038.0302
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pesticide Residues on Honey Bee (Hymenoptera: Apidae) Colony Health in France

Abstract: A 3-yr field survey was carried out in France, from 2002 to 2005, to study honey bee (Apis mellifera L.) colony health in relation to pesticide residues found in the colonies. This study was motivated by recent massive losses of honey bee colonies, and our objective was to examine the possible relationship between low levels of pesticide residues in apicultural matrices (honey, pollen collected by honey bees, beeswax) and colony health as measured by colony mortality and adult and brood population abundance. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(135 citation statements)
references
References 26 publications
5
116
1
6
Order By: Relevance
“…Thiacloprid, another neonicotinoid, is toxic to honeybees (Decourtye et al, 2010) and is also extensively used in honeybee pollinated crops (Moritz et al, 2010). Residues of these insecticides are commonly found inside the hives of managed colonies (Mullin et al, 2010;Chauzat et al, 2009), yet no clear relationship has been made between pesticides and the increased loss of managed honeybees.…”
Section: Pesticides and Chemical Sprayingmentioning
confidence: 99%
“…Thiacloprid, another neonicotinoid, is toxic to honeybees (Decourtye et al, 2010) and is also extensively used in honeybee pollinated crops (Moritz et al, 2010). Residues of these insecticides are commonly found inside the hives of managed colonies (Mullin et al, 2010;Chauzat et al, 2009), yet no clear relationship has been made between pesticides and the increased loss of managed honeybees.…”
Section: Pesticides and Chemical Sprayingmentioning
confidence: 99%
“…LD50 μg/kg based on bee weighing 0.1g -data from EPA Ecotox database, ANSES Agritox database, Greig-Smith et al (1994) (Faucon et al, 2002) 14.6-29 µg/kg tau fluvalinate (Ghini et al, 2004) 14 monitoring stations of 2 hives observed weekly, analysis of when threshold of 250 dead bees/week reached (Wiest et al, 2011)16 apiaries in Pay de Loire 145 samples (Chauzat et al, 2009) 24 apiaries at 5 sites across France to give a total of 120 hives.…”
Section: Supporting Publications 2012:en-340 19mentioning
confidence: 99%
“…In France (Chauzat et al, 2009) and (Chauzat et al, 2011) reported the levels of a range of pesticides on honey and wax samples collected from 24 apiaries at 5 sites across France, a total of 120 hives. The main types of honey were chestnut, oilseed rape, sunflower, and local mixed flower honey and 14.2% of honey samples contained two or three active ingredients had frequencies of 12.1 and 2.1%, respectively but unfortunately these were not specificd.…”
Section: 2mentioning
confidence: 99%
“…The consequences of climate change on bee honey yield are also an object of studies by various authors (Diegado et al, 2012;Paraiso et al, 2012;Switanek et al, 2017). The treatment of agricultural areas with different insecticides also has a negative effect on the quantity of bee colonies (Chauzat et al, 2009). Diseases of bees are an important factor.…”
Section: Introductionmentioning
confidence: 99%